ANALISIS PERSEPSI MASYARAKAT TERHADAP PANGAN LOKAL SAGU DI KOTA KENDARI SULAWESI TENGGARA - Abidin, Zainal (Berkala Ilmiah AGRIDEVINA, 2018)
Enhancing sago consumption as a local food must conduct as one strategy of food diversification to support self-sufficiency of rice that was reached recently. Consumption of sago is closely with community perception of sago.Â Â The research was conducted at January â Mei 2016 in Kendari city using survey method for 150 respondents that choose by stratified random sampling base on ethnic configuration. The result of research showed that the community perception level for sago local food commonly high (score 93,0). Easily to get sago local food is a higher of perception parameter (score 99,2) than others, but parameter the feeling not good if one week doesÂ not eat of sago local food is a lower perception parameter (64,8) than others. For the next,Â the effort to develop food diversification, growing and increasing community perception especially provision of raw material such us developing of sago culture is important of conduction.